Property price misalignment with fundamentals in Malta - Brian Micallef (Central Bank of Malta, 2016)
This paper computes an aggregate 'misalignment' index using a multiple indicator approach to identify under or over-valuation of house prices in Malta based on fundamentals. A total of 5 indicators are used that capture demand, supply and banking system factors: the house price-to-RPI ratio, the price-to-income ratio, price-to-construction costs ratio, dwelling investment-to-GDP ratio and the loan-to-income ratio. These indicators enter the index in 'gap' form, that is, as a deviation from their trends or long-run averages. The weights are derived using principal component analysis. Based on the Central Bank of Malta house price index, the misalignment indicator shows a period of overvaluation in house prices that peaked in 2006-2007. This disequilibrium started to be corrected following the decline in house prices, reaching a trough in 2013. Starting in 2014, however, the index started to recover such that, by end-2015, house prices were broadly in equilibrium.
Keywords: E32; E37; C01; C22; 330